Photopolymerization of dimethacrylates in the presence of 2-mercaptobenzothiazole (MBT) and 2,2’-benzothiazole disulfide (BTDS) - Andrzejewska, E.; Andrzejewski, M.; Zych-Tomkowiak, D. (Polimery, 2022)
The effect of a heteroaromatic thiol and disulfide, viz. MBT and BTDS, was preliminarily studied in the photopolymerization of tetraethylene and triethylene glycol dimethacrylates (TETGDM, TEGDM), initiated with type I (Irgacure 369) and type II (camphorquinone, CQ) photoinitiators and benzoyl peroxide (BPO) as thermal initiator in air or in Ar. Polymerization was run under 300-400 run or > 400 run irradiation (Hg and halogen lamp, resp.) and its kinetics was followed by isothermal DSC [9] (Figs. 1-3). In Ar, the additives had no influence on the Irgacure 369-initiated polymerization of TETGDM; in air, each additive retarded the polymerization and decreased the conversion of double bonds. Retardation of polymerization by additives was also observed, both in air and in Ar, in the process initiated by BPO. In the CQ-initiated polymerization of TEGDM the additives accelerated the polymerization. In air, BTDS raised the maximum polymerization rate to a value somewhat lower man did MBT, and did not reduce the induction period. In Ar, BTDS accelerated the polymerization considerably, much more then did MBT. Results are discussed in terms of the hydrogen abstraction and chain transfer reactions and also photochemical reactions of the additives.